2010
DOI: 10.1128/mcb.00848-09
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Regulation of Follicle-Stimulating Hormone β by Pulsatile Gonadotropin-Releasing Hormone Is Mediated by Functional Antagonism of bZIP Transcription Factors

Abstract: Oscillatory synthesis and secretion of the gonadotropins, follicle-stimulating hormone (FSH) and luteinizing hormone (LH), under the control of pulsatile hypothalamic gonadotropin-releasing hormone (GnRH), is essential for normal reproductive development and fertility. The molecular mechanisms by which various patterns of pulsatile GnRH regulate gonadotrope responsiveness remain poorly understood. In contrast to the ␣ and LH␤ subunit genes, FSH␤ subunit transcription is preferentially stimulated at low rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…Maybe due to its crucial role in the regulation of fertility, the FSHB gene sequence is highly conserved in humans [75,121] and very few inactivating mutations were detected [75,[122][123][124][125][126][127][128][129][130][131][132]. Consistent with its high conservation rate, the most frequent variants of the FSHB gene are only five worlwide, but only two are carried by about 96.6% of population samples chosen in three continents [121].…”
Section: The Fshb Genotype In Male Fertilitysupporting
confidence: 61%
“…Maybe due to its crucial role in the regulation of fertility, the FSHB gene sequence is highly conserved in humans [75,121] and very few inactivating mutations were detected [75,[122][123][124][125][126][127][128][129][130][131][132]. Consistent with its high conservation rate, the most frequent variants of the FSHB gene are only five worlwide, but only two are carried by about 96.6% of population samples chosen in three continents [121].…”
Section: The Fshb Genotype In Male Fertilitysupporting
confidence: 61%
“…Conversely, recent work has revealed that at low pulse frequency the PKA-dependent pathway mediates GnRH activation of the cAMP response element-binding protein (CREB), which results in stimulation of FSH␤ transcription (11). cAMP early repressor is thought to abrogate the preferential stimulation of FSH␤ gene expression at high GnRH pulse frequency by reducing CREB occupation of the rat FSH␤ promoter (6). In contrast, differential expression of AP1 factors and corepressors SKIL and TGIF1 was proposed to mediate GnRH pulse sensitivity of FSH␤ expression (9).…”
Section: Discussionmentioning
confidence: 99%
“…The data reported in this paper have been deposited in the Gene Expression Omnibus (GEO) database, www.ncbi.nlm.nih.gov/geo (accession number GSE52631 syndrome, and underlie the pharmacological treatment of gonadal hormone-dependent diseases, such as endometriosis and prostate cancer. Because of its biological and medical importance, the frequency system underlying gonadotropin regulation has been an area of study for decades, and several factors have been proposed to contribute to FSH␤ frequency sensitivity (2,(5)(6)(7)(8)(9)(10)(11). The major information processing properties of molecular signaling networks are largely determined by simple network motifs, and specific feedback or feed-forward circuits are necessary to create a robust low frequency detector (12)(13)(14).…”
mentioning
confidence: 99%
“…phosphorylation, ubiquitination or sumoylation of TFs) with the potential to alter the efficiency of assembly and the stability of the multiprotein complex. It has been very well established experimentally that high GnRH pulse frequencies favour activation of the LHb promoter whereas slower pulse frequencies favour activation of the FSHb promoter both in vivo and in vitro [2,6,32,38] but the possibility that these optima themselves vary under different conditions has not been extensively explored. Thus, optimal pulse frequencies for GnRH effects differ between species [6] but to our knowledge, the possibility that they vary under different physiological conditions (i.e.…”
Section: Discussionmentioning
confidence: 99%